Intestinal Fatty acid Absorption - Ji, Yong; Li, Xiaoming; Tso, Patrick (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2009)
Dietary lipids and many lipophilic vitamins and compounds are transported in lymph by chylomicrons which are secreted by the enterocytes of the small intestine. This article reviews our current understanding of the digestion, uptake, intracellular metabolism, and packaging of dietary lipids into chylomicrons. An overview of the digestive enzymes involved in the digestion of triacylglyerol is provided. We also discuss the relative importance of vesicles and micelles in delivering the lipid digestion products for uptake by the small intestine. While there is certainly evidence for the involvement of transporters in the uptake of cholesterol by enterocytes, we believe the uptake of fatty acids is predominantly passive. The active uptake of fatty acids is only important when the luminal fatty acid concentration is very low (probably to ensure that the essential fatty acids are not lost). We also describe the roles of the various lipid esterifying enzymes in the metabolism of the absorbed partial glycerides and fatty acids. In addition, the present review illustrates the mechanism by which intracellular assembly and modification occur during the formation of chylomicrons and very low density lipoprotein. Furthermore, clinical disorders related to intestinal lipid transport are discussed. The authors' basic and clinical insights into the processes of intestinal lipid absorption provide valuable information about effective, safe ways to prevent obesity and hyperlipidemia.
Keywords: pluronic-81